2023
DOI: 10.1097/scs.0000000000009292
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Cavernous Hemangioma on the Lateral Wall of the Inferior Nasal Meatus

Abstract: The relationship of human acellular dermal matrix thickness on complication rate and patient-reported outcomes in implant-based immediate breast reconstruction. Gland Surg 2021;10:90-100 5. Park SC, Nam JS, Lee KI, et al. Effectiveness of cross-linked human acellular dermal matrix in primary and revision augmentation rhinoplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Here, we report a case of cavernous variety in the right inferior turbinate. Few previously reported cases originated from the inferior turbinate, 9–12 but Caylakli et al reported cavernous hemangioma in the middle turbinate, 13 Nakahira et al reported in vomer, 14 Graumüller et al demonstrated a case in lamina perpendicular is ossi ethmoidalis, 15 Engels et al reported a case in the sinus maxillaris, 16 and recently Yeon et al published a case report on the lateral wall of the inferior nasal meatus 17 . Extremely rare conditions are seen in patients with concomitant malformation or benign or malignant lesions in the sinonasal sinus anatomical site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we report a case of cavernous variety in the right inferior turbinate. Few previously reported cases originated from the inferior turbinate, 9–12 but Caylakli et al reported cavernous hemangioma in the middle turbinate, 13 Nakahira et al reported in vomer, 14 Graumüller et al demonstrated a case in lamina perpendicular is ossi ethmoidalis, 15 Engels et al reported a case in the sinus maxillaris, 16 and recently Yeon et al published a case report on the lateral wall of the inferior nasal meatus 17 . Extremely rare conditions are seen in patients with concomitant malformation or benign or malignant lesions in the sinonasal sinus anatomical site.…”
Section: Discussionmentioning
confidence: 99%
“…Few previously reported cases originated from the inferior turbinate, 9 , 10 , 11 , 12 but Caylakli et al reported cavernous hemangioma in the middle turbinate, 13 Nakahira et al reported in vomer, 14 Graumüller et al demonstrated a case in lamina perpendicular is ossi ethmoidalis, 15 Engels et al reported a case in the sinus maxillaris, 16 and recently Yeon et al published a case report on the lateral wall of the inferior nasal meatus. 17 Extremely rare conditions are seen in patients with concomitant malformation or benign or malignant lesions in the sinonasal sinus anatomical site. Our patient had a history of progressive right and left‐sided nasal obstruction without a history of excessive bleeding and experienced endoscopic sinus surgery removing polypoidal masses from both sides with quite excessive intraoperative bleeding from the right side that has been proven to be a cavernous hemangioma, whereas the left side polyp was proven to be an inverted papilloma.…”
Section: Discussionmentioning
confidence: 99%